Development of a GEDSI Based Science Educational Game Using RPG Maker to Improve Science Process Skills in Madrasah Ibtidaiyah - Andrian Gandi Wijanarko; Siti Anisatun Nafi’ah; Yoga Dwi Prada; Mohamad Ardin Suwandi (Universitas Syiah Kuala, 2026)
The limited availability of GEDSI-based (gender equality, disability, and social inclusion) science educational games in Madrasah Ibtidaiyah has reduced opportunities to provide inclusive and engaging learning experiences for elementary students. Existing science learning media are still dominated by conventional approaches and have not optimally integrated GEDSI principles into interactive digital games. Therefore, this study aimed to develop, determine the feasibility, and examine the effectiveness of the GESID (GEDSI-based science educational game), an RPG-based science learning game designed to support science process skills (SPS) in Madrasah Ibtidaiyah. This study employed the ADDIE research and development model consisting of analysis, design, development, implementation, and evaluation. Data were collected through teacher and student needs analysis questionnaires, material and media validation, effectiveness testing, structured observations, in-depth interviews, and document analysis. The participants were elementary students in Madrasah Ibtidaiyah under LP Ma'arif NU, Magelang Regency. The findings indicate that the GESID game successfully integrates GEDSI-based science content into an RPG learning environment. Expert validation results demonstrated that the game achieved a high level of feasibility and is appropriate for classroom implementation. The novelty of this study lies in the development of a GEDSI-based science educational game using the RPG Maker platform, which has not been previously reported. Future studies are encouraged to further develop and innovate inclusive science learning games based on GEDSI using RPG Maker or similar platforms